Analysis of the Effectiveness of Implementing Internal Control on Doubtful Receivables PT. PLN Persero ULP Belawan - Siti Aisyah; Syarifah Fadillah Natasha; Taufiq Risal; Santi Rizki; Ananda Fitriani Dewi; Nahar Maganda Saragih (PT FORMOSA CENDEKIA GLOBAL, 2023)
Internal control has an important role in the performance of state-owned companies, one of which is PT. PLN (Persero). The aim of this research is to find out in detail what causes doubtful receivables to occur every month at PT. PLN (Persero) ULP Belawan. To find out whether the role of internal control is effective in collecting doubtful receivables. To find out what obstacles the internal control system faces in minimizing doubtful receivables. Then to find out what efforts must be made so that the collection of doubtful receivables can be carried out optimally. This research approach uses a descriptive approach and uses qualitative research methods. The internal control system for doubtful receivables is implemented at PT. PLN (Persero) ULP Belawan, is quite adequate in terms of the elements of its internal control. Such as the control environment, risk assessment, control activities, information and communication, but the supervision element is still not effective.